Application of the Andragogy Principle in the Life Skills Education Program in Increasing the Self-Relience of Entrepreneurs - Adang Danial; Syaefuddin Syaefuddin; Adjid Madjid; Ahmad Hamdan (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2019)
One of the learning objectives of non-formal education is adults who have low education to be able to develop potential, knowledge, skills and life skills. The purpose of this study was to find out / see the application of the principle of andragogy in the life skills education program at LKP Anugrah Pratama, Tasikmalaya City. This study uses descriptive research methods with qualitative approaches with data collection techniques in-depth interviews, observation and documentation studies. The results of the study show that adults have knowledge and experience that can be used as a reference for the learning process. Adults have their own needs in the learning process, in this case the students want to improve their knowledge and skills in the form of sewing to improve their quality of life. So the conclusion is that the application of the principle of andragogy can make the learning process comfortable for students, because students can develop themselves according to their experiences and problems. The benefits of this research can be used for the development of adult learning especially in life skills education programs.